Al-Qur’an dan Sunnah Sebagai Sumber dan Dalil Hukum - Sugih Ayu Pratitis; Mhd. Syahnan; Nispul Khoiri; Dhiauddin Tanjung (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze the position of the Qur’an and the Sunnah as the primary sources and legal evidences of Islamic law, as well as to explain the characteristics of textual implication (dalālah al-naṣṣ) in the determination of legal rulings. This study is motivated by the continuing misunderstandings in comprehending the relationship between the Qur’an and the Sunnah and their implications for the formulation of Islamic legal rulings. The research employs a qualitative approach using a library research method, examining both classical and contemporary literature in the fields of uṣūl al-fiqh, Qur’anic exegesis, and ḥadīth studies. The analysis focuses on the definitions of the Qur’an and the Sunnah, the concepts of qaṭ‘ī al-dalālah and ẓannī al-dalālah, and the functions of the Sunnah in explaining, reinforcing, and complementing Qur’anic rulings. The findings indicate that the Qur’an constitutes the primary, normative, and universal source of Islamic law, while the Sunnah occupies the position of the second source, functioning as an interpreter, explicator, and confirmer of Qur’anic provisions. The study also reveals that legal verses in the Qur’an possess varying degrees of textual certainty, namely qaṭ‘ī, which is definitive and leaves no room for ijtihād, and ẓannī, which remains open to interpretation and ijtihād. Furthermore, the Sunnah is classified into qauliyyah, fi‘liyyah, and taqrīriyyah, each of which plays a significant role in the formation of Islamic law. This study emphasizes that a proper understanding of the sources and legal evidences of Islamic law is essential for the correct and contextual application of Sharī‘ah.